7n=42

Simple and best practice solution for 7n=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7n=42 equation:


Simplifying
7n = 42

Solving
7n = 42

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Divide each side by '7'.
n = 6

Simplifying
n = 6

 

You can always share this solution

See similar equations:

| 2x+58=7x+13 | | 8x+5=5x+23 | | n-9=10 | | 10x-17=73 | | 9x+9=63 | | 10n+4=104 | | 2x+45=6x+13 | | 3n-14=7 | | n*5=50 | | 6n+6=24 | | 2+2x=0 | | -2x+6=4(-6-8x) | | -14-6n=5-4n-3 | | a-6=-3+2a | | -4v+4v=6+v | | 7-7(1-4r)=-224 | | -6.2-3x-5.1-x=-3y-6 | | 8(y-4)=7(1+y) | | -7(n+6)-(5-3n)=-5n | | 2y+5=19 | | (6y+6)-(8y+8)= | | 6+5c=-29 | | (4y+4)-(6y+2)= | | (y-5)-(8y+8)= | | 12+2b=2(6+2b)+4 | | (4y-9)-(8y-2)= | | 2m+1+3m=5m-3 | | -3+6r=-5+7r+1+8 | | -x-(3+4x)=-3(5-9x)+2 | | k+2k+15=k-1 | | 6x-(3x-2)=17 | | 4-3(x-2)=5 | | 3z-7z=-2z-6+4z | | 4x+7=(-17) | | 8x+14=(-138) | | -7z+5z=8z-2-4z | | (3y-11)+(4z+2)=90 | | 6x-21=33+9x | | 2(x+4)=12 | | 8+6p=p+p | | 16x-19=113-6x | | (3y-11)+(y+19)=90 | | (3y-11)=(y+19) | | 5+5= | | .2(15z-5)=4(4z+1) | | .33(6x+3)=2x-5 | | 5t-5=5t+7 | | 2y+18=12-6(y+7) | | -.75(8x-12)=5x-2 | | .5(12n-2)=5n-7 | | 11w+2(w+1)=5w-6 | | 4(2m+5)=3m-5 | | 60=21+3t | | 10x-5y=95 | | 2(x+x+2)=x+1+18 | | 3(x+2)-4(3+2x)=0 | | 4x-3=4(5-x) | | 85=21+4n | | 3(x-5)=2x-x | | 5x-7=2(4+x) | | 7-5x=2(4+x) | | 2(x+x+3)=x+2+18 | | x-2.8=1.6 | | 3(5-x)=2x-x | | 3x+12=-10 |

Equations solver categories